ANIMATION PRODUCT DEVELOPMENT STUDY BASED ON LOCAL CULTURE IN MALANG - Sumarsono Soemardjo (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
Animation products in Malang is the field of entertainment business that has a fairly bright prospect in its development in the local, national and global markets. Although at this point the animation market in general is still dominated by a wide range of products from developed countries with capitalist tenet, like the United States, nowadays, there is a growth of local culture-based animation producers in Malang, still searching for various marketing alternatives. This qualitative research study aims to answer :( 1 ) . The perception/view of business people in facing the animation products domination in the national market, and ( 2 ). The experience of animation producers in developing local culture-based animation in Malang, in order to compete in the global market . The results showed : animation producers in Malang shared the same view that the local culture-based animations are still having trouble in its market share. However, based on experience and hard work through innovative ways to improve the quality of the local culture-based animation in Malang, it is hoped to be able to penetrate the global market. Keywords: Product Animation, Cultural Commodification Local, National and Global Markets